Transmisja cen w łańcuchu dostaw na przykładzie branży drobiarskiej w latach 2000-2004 - Szpon, Jakub (Prices Coverage in the Supply Chain on the Example of Poultry Branch in the Years 2000-2004, 2006)
Qualification of supply chain participants enables not only to analyse technical - organizing conditions of material stock flow, but also costs and benefits arrangement. In complete agriculture production there are no restrictions of entities integration. Nowadays there is a trend of activities consolidation in the production vector flow, financial store and "process motion" information. Dependence on appearance between link of supply chain of individual entities depends on a changing price of offered products. Coverage prices observation enables a steady risk arrangement between integrated entities in the supply chain.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 392-398